The mental game of golf: Understanding relationships between self-efficacy, fear of failure, competitive state anxiety, and flow - Lee, D.; Kang, S. (Perceptual and Motor Skills, 2024)
Our purpose in this study was to investigate the relationship between self-efficacy, fear of failure, competitive state anxiety, and flow among elite golfers. We surveyed 375 elite golfers (N = 375; male = 187, female = 188) who were registered with the Korean Sports and Olympic Committee, and we analyzed their survey responses using descriptive statistics, confirmatory factor analysis, correlation analysis, and structural equation modelling. As expected, we found golf self-efficacy (GSE) to be significantly related to fear of failure (FOF). We also found FOF and competitive state anxiety (CSA) significantly related to flow. Finally, we verified a suspected hierarchical or mediating effect in these relationships such that we verified predictive relationships of flow as follows: GSE -> FOF -> CSA -> Flow. These golfers` self-efficacy had a buffering effect of lowering their FOF and CSA in the pathway toward flow. A suggested implication of these findings is that to enhance a golfer`s performance by minimizing interfering psychological factors, it is essential to boost their self-efficacy.